2014
DOI: 10.1177/0148607114550692
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Multidisciplinary Parenteral Nutrition Care Provided at a Distance via Mobile Tablets

Abstract: Background Determining the costs of healthcare delivery is a key step for providing efficient nutrition-based care. This analysis tabulates the costs of delivering home parenteral nutrition (HPN) interventions and clinical assessments through encrypted mobile technologies to increase patients’ access to healthcare providers, reduce their travel expenses, and allow early detection of infection and other complications. Methods A traditional cost-accounting method was used to tabulate all expenses related to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Tablets have been widely used for telemedical purposes, targeting both health care professionals [34–37] and patients [3840]. …”
Section: Discussionmentioning
confidence: 99%
“…Tablets have been widely used for telemedical purposes, targeting both health care professionals [34–37] and patients [3840]. …”
Section: Discussionmentioning
confidence: 99%
“…The costs for setting up mobile videoconferencing sessions can be offset by saving out-of-pocket travel costs and travel time [81], as well as providing the opportunity for the health professionals to meet with the whole family [82]. Previous research found the average out-of-pocket health care costs for these patients was $17,000 annually with travel to local and distant specialists [83].…”
Section: Discussionmentioning
confidence: 99%
“…The research framework guiding the 2 trials was the family home care model 38 . The 2‐pronged intervention in each trial translates evidence‐based strategies to (1) deliver synchronous facilitated support group videoconferencing sessions via the tablets (eg, iPad mini) and (2) upload the asynchronous IVhomeCare interventions (eg, written information, forms, illustrations, and graphics) to the mobile device Internet links 39 , 40 …”
Section: Telemedicine Support Groups For Hpn Users and Caregivers: Twmentioning
confidence: 99%
“…The average cost per iCare participant for 3 iPad visits based on equipment and mailing, connection, and personnel costs was $376. Detailed costs for the tablet visual meetings were published in the Journal of Parenteral and Enteral Nutrition 40 and were similar per visit.…”
Section: Delivering the Hpn Telemedicine Support Groups: Processmentioning
confidence: 99%